Clinical, immunological and genomic analysis of the post vaccinated SARS-CoV-2 infected cases with Delta derivatives from Maharashtra, India, 2021. Issue 1 (July 2022) - Yadav, Pragya D.; Sahay, Rima R.; Agrawal, Sachee; Shete, Anita; Adsul, Balkrishna; Tripathy, Srikanth; Nyayanit, Dimpal A.; Manrai, Manish; Patil, Deepak Y.; Kumar, Sanjay; Marwah, Vikas; Sapkal, Gajanan N.; et al.
Highlights: Globally breakthrough infections have occurred post COVID-19 vaccinations. Delta and delta derivatives predominated amongst the infected cases. All the cases presented with mild disease and had very low mortality. Covishield and Covaxin vaccination could able to prevent the severe disease. Assessment of immune response demonstrated need for booster dose.